math
posted by Sara .
verify that the function f and g are inverse of each other by showing f(g(x)) and g(f(x)) =x
f(x)= 62/5x g(x)=155/2x

just plug and chug:
(I rewrite 2/5x as 2x/5 to avoid ambiguity)
f(g) = 6  2g/5 = 6  2(15  5x/2)/5
= 6  (30  5x)/5 = 6  (6  x) = x
g(f) = 15  5f/2 = 15  5(6  2x/5)/2
= 15  (30  2x)/2 = 15  (15  x) = x
Respond to this Question
Similar Questions

algebra
1 (a) A function passes through the points (0, 5), (1, 0), (2, 7). Use finite differences to determine the equation of the function. (b) Draw the graph of the function. (c) Draw the inverse on the graph. (d) Show at least two different … 
math
The cost of producing q articles is given by the function C=f(q)=100+2q. (A) Find the formula for the inverse function. (B) Explain in practical terms what the inverse function tells you. I am pretty sure the answer to A is f^1(C)=C/250 … 
algebra 2
for each function, find an equasion for the inverse. then use composition to verify that the equasion you wrote is the inverse. f(x)=10x6 
algebra 2
for each function, find an equasion for the inverse. then use composition to verify that the equasion you wrote is the inverse. g(x)=6x+5 please explain how you got the answer 
algebra 2
for each function, find an equasion for the inverse. then use composition to verify that the equasion you wrote is the inverse. f(x)=14.4x 
Algebra
I have to find the inverse function of f(x)=34x. I got y=3x/4 for the function. I then have to plug it back into the function and verify that it is the inverse. So I wrote (34(3x))/4. This resulted in (3+x)/4=x. I tried isolating … 
College Algebra
verify that the functions of f and g are inverse of each other by showing that f(g(x))=x and g(f(x))=x; f(x)=In(x1),g(x)=1+e^x 
College Algebra
Verify the function f and g, are inverses of each other by showing that f(g(x))=x and g(f(x))=x Graph the functions. f(x)=6/(1x) g(x)=(16/x) 
Maths B
(a) What is the inverse of the function y = 3x2 ? 
Math
Find the inverse function of f(x)=(x+4)/(2x5) and then verify your result using: f(f^1(x))=x and f^1(f(x))=x. Please an answer fast